PENGARUH KOHESIVITAS KELOMPOK DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA MELALUI TURNOVER INTENTION KARYAWAN PT. PURNAMA INDONESIA DI SIDOARJO - Frisca Waty Simarmata; Agus Rahman; Ike Kusdyah (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
The purposes of this research are to determine the effect of group cohesiveness on employee productivity, group cohesiveness on employee turnover intention, job satisfaction on employee productivity, and job satisfaction on employee turnover intention. Furthermore, this research also aims to determine the effect of turnover intention on employee productivity, group cohesiveness on work productivity through employee turnover intention, and the effect of employee satisfaction on work productivity through employee turnover intention. The analysis result shows that group cohesiveness affects PT. Purnama Indonesia’s employee productivity. It also indicates that the group cohesiveness also affects the employee turnover intention, the job satisfaction also affects the employee productivity, and It shows that job satisfaction affects PT. Purnama Indonesia’s employee turnover intention. Furthermore, the result implies that the group cohesiveness has an effect on PT Purnama Indonesia’s employee productivity through turnover intention. Observed from turnover intention, it can be concluded that employee satisfaction affects productivity.